Strategi Pengembangan Kampung Wisata Pancer di Kota Serang Sebagai Destinasi Wisata - Pakpahan, Rosdiana; M.S Lagalo, Anggraeni (Program Studi S1 Pariwisata, Universitas Muhammadiyah Gorontalo, 2023)
Pancer tourism village is not separated from the synergy that is built between the governments, community, and Pokdarwis (Kelompok Sadar Wisata) based on empowerment. Pancer Tourism Village has several tourist attractions that can be enjoyed by tourists such as marine tourism, selfie tourism, and fishing. With the existence of the Pancer tourism village, it can be one of the closest tourist alternatives for the people of Serang City and also can increase the local budget revenues of Serang City. The village with the social conditions of the fishing community is expected to be able to support the local economy.In this research, the researcher will discuss development strategy which is conducted in the development of the Pancer tourism village. As the researcher’s goal is to collect the development strategy plan of tourism village in Serang City especially Pancer tourism village. The data analysis technique used in this research is qualitative data analysis techniques using primary data and secondary data. This research produced results, that the Pancer tourism village is the only tourist village in the Serang City that already has marine tourism as its main destination. The Pancer tourism village still needs cooperation with outside parties to be more advanced in its development.